Efektifitas Wisata dalam Pertumbuhan Ekonomi di Tapanuli Selatan - Batubara, Damri; Hardana, Ali (El-kahfi | Jurnal Ekonomi Islam, 2024)
Tourist attractions function as a multiplier effect on various economic activities. Increase the country's foreign exchange, create employment opportunities and reduce poverty levels. South Tapanuli has good, beautiful and natural tourist attractions. So it is very promising and has the potential to revive the community's economy. However, amidst this potential, there is actually an increase in poverty and unemployment. The aim of this research is to determine the effectiveness of tourism in economic growth and the formulation of the problem, how effective tourism is in economic growth in South Tapanuli. The research method is descriptive qualitative, the data sources are primary and secondary. Meanwhile, data collection techniques are observation, interviews and documentation. Data processing and analysis techniques, data editing, data reduction, data description and drawing conclusions. The result is that tourist attractions have not yet fully contributed effectively to increasing the community's economic growth. Because there are internal factors that have not been fulfilled. Such as, lack of human resources and budget funds. Likewise external factors. Such as weaknesses in skills, difficult accessibility, seasonal tourist activities and inadequate facilities.